Utilization of Educational Games in the Implementation of Strengthening Character Education - Sulastri Sulastri; Sukestyarno YL; Nurhasanah Nurhasanah (CV. Tripe Konsultan, 2022)
Educational games are simulation-based media designed to simulate existing problems so that the essence of knowledge is obtained that can be used to solve problems. This study aims to produce a Character Education Strengthening device product in the form of a syllabus, teacher guide book, student guide book assisted by appropriate educational games, which have a level of product validity and practicality. Obtaining the product begins with conducting a preliminary study through literature studies, learning observations, testing to validators, limited-scale trials, revisions, products, main-scale trials, and final products. This study uses the type of research and development with the flow of Borg & Gall with stages from preliminary studies to field trials. The data collection instruments used were validation sheets, student response questionnaires, teacher responses, and observation sheets for the teacher's ability to use the product. The results showed that the product development in the form of a syllabus supplement obtained a score of 82.75%. At the same time, the product development of the Character Education Strengthening guidebook for teachers got a validation value from the validator of 84.66%. It obtained a validation value from the validator of 81.23%. Experimental test data for student responses scored 83.80%, and teacher responses reached 86.90%. It means that the development product falls into the very valid, very practical, and feasible.